Socio-Philosophical Essence and Legal-Cultural Significance of Reforms in Rural Agro-Development - Abdurakhmanova Nodirakhan Khusnutdinovna (Genius Journals, 2023)
The fundamental changes, reforms carried out in the new Uzbekistan also covered the consciousness, thinking, life positivity and agro-development of the rural population. Rural agrotechnics remains the main industry supplying our country with food, nozu favors and the necessary products for production.
Keywords: favors; production; remains; industry